Dehydrocoupling of dimethylamine-borane promoted by manganese(II) m-terphenyl complexes - Sharpe, Helen R.; Geer, Ana M.; Blundell, Toby J.; Hastings, Fiona R.; Fay, Michael W.; Rance, Graham A.; Lewis, William; Blake, Alexander J.; Kays, Deborah L. (Royal Society of Chemistry, 2017)
Two- and three-coordinate manganese m-terphenyl complexes are precatalysts for the dehydrogenation of dimethylamine-borane (Me2NH·BH3) affording one equivalent of molecular hydrogen and half an equivalent of [Me2N–BH2]2. Experimental studies into the nature of the catalyst indicate that small changes in the coordination environment give rise to significant differences in the reaction mechanism, occurring through a homogeneous mechanism for two-coordinate precatalysts, whilst for the three-coordinate species a heterogeneous mechanism takes place where nanoparticles are responsible for the catalysis.